Financial Institutions and Economic Growth: An Empirical Analysis of Indian Economy in the Post Liberalized Era - Kaushal, Shrutikeerti; Ghosh, Amlan (International Journal of Economics and Financial Issues, 2016)
Development of insurance and banking institutions is one of the fundamental constituents that plays an important role in stimulating financial development and thereby the growth of the economy in any country. However the causal effect of these financial institutions can’t be generalized as the development of financial institution is quite different in nature and scale in different countries. This paper attempts to examine the relationship between financial institutions and economic growth in the Indian economy. We find that there exists a long run relationship and insurance institutions do promote the economic growth and vice-versa. It is also found that it is growth in the economy that causes development of banking institutions. Keywords: Economic Growth, Financial Institutions, Banks, Insurance, Time Series, India. JEL Classifications: C22, E44, G20, G21, G22, O16